2006
DOI: 10.1021/jp0639750
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization of Nanowire Synthesis Using Low-Melting Point Metals

Abstract: In this paper, we provide a theoretical basis using thermodynamic stability analysis for explaining the spontaneous nucleation and growth of a high density of 1-D structures of a variety of materials from lowmelting metals such as Ga, In, or Sn. The thermodynamic stability analysis provides a theoretical estimate of the extent of supersaturation of solute species in molten metal solvent. Using the extent of maximum supersaturation, the size and density of critical nucleus were estimated and compared with exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…In order to determine the doping concentration, electronic transport measurements should be realized. Preliminary studies corroborate the potential of gallium as a catalyst for the synthesis of silicon nanowires [26,27,31,32]. As an example, extensive carpets of nanowires have been realized by exposing a gallium coated silicon wafer to high power hydrogen plasma [31].…”
Section: Introductionmentioning
confidence: 68%
“…In order to determine the doping concentration, electronic transport measurements should be realized. Preliminary studies corroborate the potential of gallium as a catalyst for the synthesis of silicon nanowires [26,27,31,32]. As an example, extensive carpets of nanowires have been realized by exposing a gallium coated silicon wafer to high power hydrogen plasma [31].…”
Section: Introductionmentioning
confidence: 68%
“…The pyrolysis experiments clearly showed that Ga droplets act as an initiator (catalyst) for the GaSb nanowire growth. Ga droplets have been shown in the past to initiate nanowire growth of a variety of materials such as Si and Ge [28]. Therefore we were interested in the deposition of small Ga droplets with a defined diameter.…”
Section: Resultsmentioning
confidence: 99%
“…We have not been able to significantly decrease the diameter of the nanowires by using lower thicknesses of cobalt and nickel films, although as mentioned above the catalytic oxidation of VO 2 yields thinner wires as compared to the use of V 2 O 5 as the precursor. Chandrasekaran et al have theoretically derived an expression for the nanowire diameter ( d ) as a function of the catalyst molar volume ( V m ), interfacial energy ( σ ), and the ratio of the solute concentration at the point of instability to the corresponding equilibrium solubility ( X / X ′) at a given temperature T 24 …”
mentioning
confidence: 99%